1978
DOI: 10.1093/nar/5.9.3237
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for 7-methylguanosine in translation of globin mRNA in vivo

Abstract: The 7-methylguanosine (m G) residue present in the m G ppp X-"CAP" structure of rabbit globin mRNA was removed quantitatively by periodate oxidation followed by a-elimination in the presence of cyclohexylamine. The RNA thus treated was intact and exhibited no signs of degradation as examined by polyacrylamide gel electrophoresis in formamide. Assay for protein synthesis using a wheat germ cell-free system showed that the globin mRNA lacking m7G had lost most of its messenger activity. Identical treatment,of sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…This work shows that the in vivo structural requirements of mRNA resulting in maximal translation observed in XenoQpus oocytes also holds true for plant and animal cells. The requirement for a 5' cap observed here is similar to that found for mRNAs injected into oocytes (30,32,44). However, RNA expression in both plant and animal cultured cells shows a much greater dependence on the presence of a poly A tail than has been previously described in Xenopus oocytes (36).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This work shows that the in vivo structural requirements of mRNA resulting in maximal translation observed in XenoQpus oocytes also holds true for plant and animal cells. The requirement for a 5' cap observed here is similar to that found for mRNAs injected into oocytes (30,32,44). However, RNA expression in both plant and animal cultured cells shows a much greater dependence on the presence of a poly A tail than has been previously described in Xenopus oocytes (36).…”
Section: Discussionsupporting
confidence: 82%
“…We have investigated the use of another technique, electroporation, to introduce mRNAs into eukaryotic cells. Electroporation is the application of an electric field to reversibly permeabilize biomembranes (18) and has been indicated that the cap present at the 5' end of cellular and many viral mRNA molecules as a 5' to 5' 7m GpppN linkage is important both for RNA stability and translation initiation, although there are naturally occurring uncapped viral mRNAs (30)(31)(32)(33). The role of the poly adenylate residues at the 3' end (poly A tail) of mRNAs is less understood ( 34,35).…”
Section: Iniroducfionmentioning
confidence: 99%
“…The resulting decapped RNAs would likely be more susceptible to degradation by cellular nucleases, as it has been shown that the 5' cap structure stabilizes RNAs against nucleolytic degradation both in vivo and in cell extracts (12,20). Direct evidence in support of this hypothesis would be the identification in virus-infected cells of nuclear ALV and ,-actin transcripts lacking 10 (18).…”
Section: Resultsmentioning
confidence: 99%
“…In general, there is good agreement that an intact 5' cap is essential for mRNA stability, although the extent of destabilization attributable to decapping varies significantly for different mRNAs (17,19,23,36,40,48). The hypothesis that mRNA stability is a function of target size was initially supported by studies of mRNA populations (52,58,78,81).…”
Section: Discussionmentioning
confidence: 99%